Halloysite-based adsorbent as well as preparation method and application thereof
By loading boehmite-type alumina on the surface of Elosite and calcining and activation, a composite adsorbent with activated alumina supported on Elosite was prepared, which solved the problem of high fluorine removal cost and low efficiency in the prior art, and achieved an efficient and economical fluorine ion removal effect.
Patent Information
- Application Number
- CN202411861552.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-17
AI Technical Summary
In the prior art, when single activated alumina or elocide is used as a fluorine removal agent, the fluorine removal cost is high and the fluorine removal efficiency is low.
通过共沉淀法在埃洛石表面负载勃姆石型氧化铝,并通过煅烧活化制备出活性氧化铝负载在埃洛石的内外管壁上的复合吸附剂。
The micropore ratio and adsorption performance of the adsorbent material are improved, efficient removal of fluorine ions is achieved, production costs are reduced, and good fluorine removal effect is shown in acidic and alkaline environments.
Smart Images

Figure CN119608103A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of defluoridating agent materials, and in particular to a halloysite-based adsorbent and a preparation method and application thereof. Background Art
[0002] With the rapid development of emerging industries such as semiconductors in my country, fluoride-containing wastewater has gradually become an important source of environmental fluoride pollution, which poses a severe challenge to human survival and safety. The high-concentration fluoride ion removal technology currently in practical use is mainly the pharmaceutical method, but it can usually only treat fluoride ions to about 10 mg / L, which is much higher than the 1.5 mg / L drinking water standard set by the World Health Organization. In order to obtain low-fluoride water, the water pre-treated by the pharmaceutical method needs to be further deeply defluorinated. Among all the methods, the adsorption method has a simple process, easy operation and low cost, and has attracted much attention. Among them, the development of efficient fluoride ion adsorption materials is the key to achieving deep defluorination.
[0003] Activated alumina has a high specific surface area and good fluorine removal performance, and is often regarded as an ideal material for deep defluorination. However, its high synthesis cost, narrow adsorption pH range and easy agglomeration limit its actual defluorination effect. The fluorine removal performance of alumina can be improved by using methods such as morphology control, pore formation and composite.
[0004] Clay minerals such as kaolinite, illite, attapulgite and halloysite are characterized by abundant reserves, low cost and environmental friendliness. Among clay minerals, halloysite has attracted extensive attention due to its unique tubular morphology and is often used in chemical catalysis, antibacterial and anti-inflammatory, drug delivery, wastewater treatment and other fields, but its fluoride removal capacity is relatively low. Summary of the invention
[0005] The present invention provides a halloysite-based adsorbent and a preparation method and application thereof, which effectively solves the technical problems of high defluorination cost and low defluorination efficiency when single activated alumina or halloysite is used as a defluorination agent. The present invention uses natural tubular halloysite mineral as a carrier, first loads boehmite-type alumina on the surface of the halloysite by a simple co-precipitation method, and then further calcines and activates to prepare a composite adsorbent in which activated alumina is loaded on the inner and outer tube walls of the halloysite.
[0006] The first object of the present invention is to provide a method for preparing a halloysite-based adsorbent, comprising the following steps:
[0007] The soluble Al 3+ The salt solution is dropped into 50℃~95℃ halloysite and alkali metal Cl - In the suspension formed by the salt solution, the pH value is controlled at 8-11, and the coprecipitation reaction is carried out. 3+ With Cl - Formation of [AlCl4] -The ligand is then hydrolyzed to obtain boehmite-type alumina, which is then loaded on halloysite to obtain a composite product;
[0008] The composite product is calcined at 400-700° C. to obtain a halloysite-based adsorbent.
[0009] As a preferred embodiment, the alkali metal Cl - Cl in salt solution - The concentration of Al is 0.01-0.2 g / mL, and the soluble Al 3+ Al in salt solution 3+ The concentration of the alkali metal Cl is 10 to 100 mol / mL. - Salt solution and soluble Al 3+ The volume ratio of the salt solution is 1-5:1-5.
[0010] As a preferred embodiment, the halloysite and the alkali metal Cl - The dosage ratio of the salt solution is 0.2-5g:30ml.
[0011] As a preferred embodiment, the coprecipitation reaction time is 10 min to 24 h.
[0012] As a preferred embodiment, the calcination time is 1 to 6 hours.
[0013] As a preferred embodiment, the soluble Al 3+ The salt is one or more of aluminum sulfate, aluminum nitrate, aluminum chloride and alum.
[0014] As a preferred embodiment, after the coprecipitation reaction is completed, centrifugation is performed to obtain a primary product, and the primary product is washed and dried at 50° C. to 60° C. overnight to obtain a composite product.
[0015] The second object of the present invention is to provide a halloysite-based adsorbent prepared by the above preparation method.
[0016] The third object of the present invention is to provide a use of the above-mentioned halloysite-based adsorbent in removing fluoride ions in water.
[0017] As a preferred embodiment, the concentration of fluoride ions in the water body is ≤10 mg / L.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The present invention firstly reacts halloysite with alkali metal Cl - The salt solution is mixed to obtain a suspension; the soluble Al 3+The salt solution is dripped into the suspension, the pH value is controlled to be 8-11, a coprecipitation reaction occurs, and the alkali metal Cl is added - Salt, on the one hand, is conducive to the chloride ion and Al 3+ Prioritizes the formation of [AlCl4] - The ligand is slowly hydrolyzed to generate boehmite, which is convenient for migration to the surface of halloysite to form a load, thereby obtaining a composite product; on the other hand, it can increase the viscosity of the solution, reduce the continuity of boehmite, and facilitate the subsequent formation of an activated alumina nanostructure; the composite product is heated to 400°C to 700°C for calcination to obtain a halloysite-based adsorbent. The crystal form of the loaded alumina synthesized under the condition of pH=8-11 in the present invention is boehmite, and calcination at 400°C to 700°C can convert it into activated alumina with greater fluoride ion adsorption activity, and the activated alumina is mainly loaded in the inner / outer tube of the halloysite, which is a wormhole porous structure. At the same time, the loading of the activated alumina increases the micropore ratio of the adsorbent material, thereby improving the adsorption performance.
[0020] (2) The present invention only uses conventional soluble aluminum salts, alkali metal chlorides and natural halloysite minerals as reaction reagents and raw materials, instead of expensive metal salts and artificial synthetic carriers. The synthesis method is simple, no special equipment is required, and the production cost is effectively reduced. The present invention uses tubular halloysite as a carrier, which effectively improves the dispersibility of activated alumina nanoparticles and reduces their agglomeration; the loaded alumina has porous wormhole characteristics, and exists in the inner / outer tubes of the halloysite at the same time, and the crystal form is the γ type that is most favorable for fluoride ion adsorption, so the adsorption efficiency is high and the adsorption capacity is large, and the fluoride-containing wastewater with a fluoride ion concentration of less than 10 mg / L can be deeply defluorinated to less than 1 mg / L. In addition, compared with pure alumina, the amount of alumina used in the halloysite-based composite defluoridant is reduced, so the price of the defluoridant per unit mass is significantly reduced.
[0021] (3) The halloysite-based adsorbent prepared by the present invention has better fluoride removal performance. It can effectively remove fluoride ions in water bodies in both acidic and alkaline environments. In a solution environment of pH=3, it can still maintain a fluoride ion removal rate of more than 98% under a lower dosage of 0.125 g / L. In the defluorination process, it is not interfered by other coexisting anions such as nitrate, carbonate, bicarbonate and sulfate, and can specifically remove fluoride ions in water bodies. Under low-dose usage, the fluoride removal efficiency of the halloysite-based adsorbent prepared by the present invention is also greater than that of commercial activated alumina balls, which has obvious cost advantages.
[0022] (4) In the process of removing fluoride ions from water, the adsorption of fluoride ions did not change the physical structure of the halloysite-based adsorbent material. The fluoride ions were first adsorbed on the inner and outer tube surfaces and edge parts of the adsorbent material through physical action, and then the Al-coordinated OH in the halloysite-based adsorbent material and F -Exchange occurs, thereby firmly binding to fluoride ions and achieving the effect of removing fluoride ions from the water. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Transmission electron microscope images of the halloysite-based adsorbent HA8-600 and the raw material halloysite H prepared in Example 1 of the present invention; wherein, Figure a is the local morphology of the halloysite H with a tubular morphology; Figures b and c are the local morphologies of the halloysite-based adsorbent HA8-600 with alumina loaded inside and outside the tubes; Figure d is the activated alumina with a porous wormhole morphology in the halloysite-based adsorbent HA8-600; Figure e is the lattice fringe image of alumina in the halloysite-based adsorbent HA8-600.
[0024] Figure 2 1 is the XRD spectra of halloysite (H), the composite product (HA8) and the halloysite-based adsorbent (HA8-600) in Example 1 of the present invention.
[0025] Figure 3 It is the infrared spectra of halloysite (H), composite product (HA8) and halloysite-based adsorbent (HA8-600) in Example 1 of the present invention.
[0026] Figure 4 1 and 2 are nitrogen adsorption isotherms of halloysite (H), the composite product (HA8) and the halloysite-based adsorbent (HA8-600) in Example 1 of the present invention.
[0027] Figure 5 This is a pore size distribution diagram of halloysite (H), composite product (HA8) and halloysite-based adsorbent (HA8-600) in Example 1 of the present invention.
[0028] Figure 6 It is a comparison chart of the fluoride removal rates of halloysite (H), composite product (HA8) and halloysite-based adsorbent (HA8-600) in Example 1 of the present invention under the conditions of dosage of 0.5 g / L, defluoridation time of 6 h, temperature of 30°C, initial concentration C0 of fluoride ion solution of 10 mg / L and pH of 4.
[0029] Figure 7 The figure is a comparison chart of the fluoride removal rates of the halloysite-based adsorbent (HA8-600) prepared in Example 1 of the present invention in water bodies with different pH values under the conditions of a dosage of 0.5 g / L, a fluoride removal time of 6 h, a temperature of 30°C, and an initial fluoride ion solution concentration C0 of 10 mg / L.
[0030] Figure 8 Under the conditions of pH 4, defluorination time of 6 h, temperature of 30 ° C, and initial concentration of fluoride solution C0 of 10 mg / L, the fluoride removal rate (Removal) and equilibrium adsorption capacity (q) of the halloysite-based adsorbent prepared in Example 1 of the present invention at different dosages are shown in Table 1.e ) comparison chart.
[0031] Fig. 9 This is a graph showing the influence of coexisting anions in water on the fluoride removal performance of the halloysite-based adsorbent prepared in Example 1 of the present invention under the conditions of a dosage of 0.5 g / L, a pH value of 4, a fluoride removal time of 6 h, a temperature of 30°C, and an initial concentration C0 of the fluoride ion solution of 10 mg / L.
[0032] Fig.10 This is a comparison chart of the fluoride removal performance of the halloysite-based adsorbent HA8-600 prepared in Example 1 of the present invention and a commercial activated alumina defluoridation agent under more optimal pH conditions (pH=3); wherein the defluoridation time is 6 hours, the temperature is 30°C, and the initial concentration C0 of the fluoride ion solution is 10 mg / L. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.
[0034] In view of the technical problems mentioned in the background technology of the present invention: when activated alumina is used as a defluorinating agent, its synthesis cost is high, the adsorption pH range is narrow, and it is easy to agglomerate, resulting in poor defluorinating effect; when halloysite is used as a defluorinating agent, its defluorinating capacity is low, the present invention provides a halloysite-based adsorbent and its preparation method and application.
[0035] The technical solution of the present invention is now analyzed and explained in detail.
[0036] The present invention first provides a method for preparing a halloysite-based adsorbent, comprising the following steps:
[0037] The soluble Al 3+ The salt solution is dropped into 50℃~95℃ halloysite and alkali metal Cl - In the suspension formed by the salt solution, the pH value is controlled at 8-11, and the coprecipitation reaction is carried out. 3+ With Cl - Formation of [AlCl4] - The ligand is then hydrolyzed to obtain boehmite-type alumina, which is loaded on halloysite and centrifuged to obtain a primary product, which is washed and dried overnight at 50°C to 60°C to obtain a composite product; the temperature of the above suspension is 50°C to 95°C. If the reaction temperature is too high, such as above 100°C, the water will evaporate quickly because the reaction is an open system; otherwise, a high-pressure reactor is required, which will increase the production cost. If the temperature is too low, it will take a long time, which will slow down the production efficiency.
[0038] The composite product is calcined at 400-700° C. to obtain a halloysite-based adsorbent.
[0039] In the above technical scheme, the crystal form of the loaded alumina synthesized under the condition of pH = 8 to 11 is boehmite, and calcination at 400°C to 700°C can convert it into activated alumina with greater adsorption activity for fluoride ions. The activated alumina is mainly loaded in the inner / outer tubes of halloysite, which is a wormhole porous structure. At the same time, the loading of activated alumina increases the micropore ratio of the adsorbent material, thereby improving the adsorption performance.
[0040] It should be emphasized that the alkali metal Cl - Cl in salt solution - The concentration of Al is 0.01-0.2 g / mL, and the soluble Al 3+ Al in salt solution 3+ The concentration of the alkali metal Cl is 10 to 100 mol / mL. - Salt solution and soluble Al 3+ The volume ratio of the salt solution is 1-5:1-5. If Cl - If the concentration is too low, it is not conducive to the formation of nano-load on the halloysite surface by the method of "forming ligands first and then slowly hydrolyzing". - If the concentration is too high, the preparation time will increase and the production cost will rise. 3+ The concentration is too low, and the amount of activated alumina finally loaded on the halloysite surface is too small, resulting in low overall adsorption efficiency; Al 3+ When the concentration is too high, the formed active alumina is easy to agglomerate on the surface of halloysite, and the surface active sites are reduced.
[0041] It should be emphasized that the halloysite and the alkali metal Cl - The dosage ratio of the salt solution is 0.2-5 g:30 mL. If the dosage of halloysite is less than 0.2 g, it will cause waste of alkali metal chloride and aluminum salt; if the dosage of halloysite is more than 5 g, it will inevitably cause waste of halloysite.
[0042] As a preferred embodiment, the coprecipitation reaction time is 10 minutes to 24 hours. If the time is too short, the boehmite loaded on the halloysite surface is too little, and when the reaction time is greater than 24 hours, the coprecipitation reaction is already completed, and further increasing the time is not beneficial to increasing the alumina yield.
[0043] As a preferred embodiment, the calcination time is 1 to 6 hours. If the calcination time is less than 1 hour, the conversion of boehmite to activated alumina will not be complete; if the calcination time is further increased, if the calcination time is longer than 6 hours, the conversion has been completed, and further increasing the calcination time will not be beneficial to the conversion rate.
[0044] It should be noted that the soluble Al 3+ The salt is one or more of aluminum sulfate, aluminum nitrate, aluminum chloride and alum.
[0045] The technical effects of the present invention are described below in conjunction with specific embodiments and comparative examples.
[0046] Example 1
[0047] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0048] 5 g of halloysite (denoted as H) was mixed with 150 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 20 mmol / L aluminum nitrate solution was dropped into the suspension at 80° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 2 hours. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained, which was denoted as HA8; the composite product was calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent, which was denoted as HA8-600.
[0049] Example 2
[0050] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0051] 5 g of halloysite was mixed with 150 mL of a 0.01 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 20 mmol / L aluminum nitrate solution was dropped into the suspension at 80° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 2 hours. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained; the composite product was calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent.
[0052] Example 3
[0053] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0054] 5 g of halloysite was mixed with 150 mL of a 0.2 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 20 mmol / L aluminum nitrate solution was dropped into the suspension at 80° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 2 hours. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained; the composite product was calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent.
[0055] Example 4
[0056] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0057] 5 g of halloysite was mixed with 150 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 10 mmol / L aluminum nitrate solution was dropped into the suspension at 80° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 2 hours. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained; the composite product was calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent.
[0058] Example 5
[0059] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0060] 5 g of halloysite was mixed with 150 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 100 mmol / L aluminum nitrate solution was dropped into the suspension at 80° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 2 hours. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained; the composite product was calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent.
[0061] Example 6
[0062] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0063] 1 g of halloysite is mixed with 150 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 20 mmol / L aluminum nitrate solution is dropped into the suspension at 80° C., while the pH value is controlled to be 8, and a coprecipitation reaction is performed for 2 hours. After centrifugation, washing, and drying, a composite product in which boehmite is loaded on halloysite is obtained; the composite product is calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent.
[0064] Example 7
[0065] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0066] 25 g of halloysite was mixed with 150 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 20 mmol / L aluminum nitrate solution was dropped into the suspension at 80° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 2 hours. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained; the composite product was calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent.
[0067] Example 8
[0068] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0069] 5 g of halloysite was mixed with 50 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 250 mL of a 20 mmol / L aluminum nitrate solution was dropped into the suspension at 80° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 2 hours. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained; the composite product was calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent.
[0070] Example 9
[0071] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0072] 5 g of halloysite was mixed with 250 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 50 mL of a 20 mmol / L aluminum nitrate solution was dropped into the suspension at 80° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 2 hours. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained; the composite product was calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent.
[0073] Example 10
[0074] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0075] 5 g of halloysite was mixed with 150 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 20 mmol / L aluminum nitrate solution was dropped into the suspension at 95° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 10 minutes. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained; the composite product was calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent.
[0076] Embodiment 11
[0077] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0078] 5 g of halloysite was mixed with 150 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 20 mmol / L aluminum nitrate solution was dropped into the suspension at 50° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 24 hours. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained; the composite product was calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent.
[0079] Example 12
[0080] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0081] 5 g of halloysite was mixed with 150 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 20 mmol / L aluminum nitrate solution was dropped into the suspension at 80° C., while the pH value was controlled to be 11, and a coprecipitation reaction was performed for 2 hours. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained; the composite product was calcined at 600° C. for 3 hours to obtain a halloysite-based adsorbent.
[0082] Example 13
[0083] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0084] 5 g of halloysite was mixed with 150 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 20 mmol / L aluminum nitrate solution was dropped into the suspension at 80° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 2 hours. After centrifugation, washing, and drying, a composite product of boehmite loaded on halloysite was obtained; the composite product was calcined at 400° C. for 6 hours to obtain a halloysite-based adsorbent.
[0085] Embodiment 14
[0086] A method for preparing a halloysite-based adsorbent comprises the following steps:
[0087] 5 g of halloysite was mixed with 150 mL of a 0.02 g / mL sodium chloride aqueous solution to obtain a suspension; 150 mL of a 20 mmol / L aluminum nitrate solution was dropped into the suspension at 80° C., while the pH value was controlled to be 8, and a coprecipitation reaction was performed for 2 hours; after centrifugation, washing, and drying, a composite product in which boehmite was loaded on halloysite was obtained; the composite product was calcined at 700° C. for 1 hour to obtain a halloysite-based adsorbent.
[0088] In order to further illustrate the technical effect of the present invention, the present invention is also provided with a comparative example, as follows:
[0089] Comparative Example 1
[0090] Compared with Example 1, the difference is that only 5 g of halloysite is used.
[0091] The morphology and performance of the halloysite-based adsorbent prepared by the present invention were characterized and analyzed. The specific results are shown in Tables 1 and Figures 1 to 10 As shown:
[0092] Table 1 compares the adsorption rate, residual fluoride ion concentration, and alumina content loaded in the sample of the halloysite-based adsorbent HA8-600 prepared in Example 1 and commercial activated alumina under more optimal pH conditions (pH=3) (other conditions: defluorination time of 6 h, temperature of 30°C, and initial concentration C0 of fluoride ion solution of 10 mg / L).
[0093] Table 1 Comparison of fluorine removal performance of the halloysite-based adsorbent of the present invention and commercial activated alumina
[0094]
[0095] It can be seen from Table 1 that although the fluoride removal rate of HA8-600 is only slightly higher than that of commercial activated alumina, only about 8.4% alumina is loaded on halloysite, so it has obvious cost advantages; at the same time, the fluoride ion concentration in the solution after fluoride removal by HA8-600 is only 0.02 mg / L, which is far below 1 mg / L.
[0096] Figure 1 Transmission electron microscope images of the halloysite-based adsorbent HA8-600 and the raw material halloysite H prepared in Example 1 of the present invention; wherein, Figure a is the local morphology of the halloysite H with a tubular morphology; Figures b and c are the local morphologies of the halloysite-based adsorbent HA8-600 with alumina loaded inside and outside the tubes; Figure d is the activated alumina with a porous wormhole morphology in the halloysite-based adsorbent HA8-600; Figure e is the lattice fringe image of alumina in the halloysite-based adsorbent HA8-600, which proves that the loaded porous substance is activated alumina (γ-Al2O3).
[0097] Figure 2 XRD spectra of the halloysite-based adsorbent HA8-600, the halloysite raw material H, and the composite product HA8 prepared in Example 1 of the present invention. Due to the small amount of boehmite loaded, HA8 does not change significantly relative to pure halloysite H; after calcination, the halloysite is amorphous, and the diffraction peak of the activated alumina is also weak due to the small amount.
[0098] Figure 3 FTIR spectra of the halloysite-based adsorbent HA8-600 prepared in Example 1 of the present invention, the halloysite raw material H, and the composite product HA8. 1034 cm after boehmite is loaded on halloysite -1 With 1095cm -1 The Si-O-Si stretching vibration peak at HA8-600 is enhanced due to the hydrogen bonds between the surface-loaded boehmite and the silicon-oxygen tetrahedrons on the halloysite surface; after further calcination, both halloysite and boehmite are dehydrated, so some peaks in HA8-600 disappear.
[0099] Figure 4The nitrogen adsorption isotherms of the halloysite-based adsorbent HA8-600 prepared in Example 1 of the present invention, the halloysite raw material H, and the composite product HA8. The nitrogen adsorption results correspond to type IVa of the IUPAC classification, which corresponds to the mesoporous characteristics of halloysite. In the stage of high relative pressure, the adsorption amount gradually increases; and in these stages, the desorption also gradually decreases, forming a hysteresis loop. This phenomenon is related to capillary condensation and mesoporous adsorption and desorption, and is therefore a typical feature of mesoporous adsorption.
[0100] Figure 5 The pore size distribution diagram of the halloysite-based adsorbent HA8-600, the halloysite raw material H, and the composite product HA8 prepared in Example 1 of the present invention. When the halloysite is loaded with boehmite and calcined, the pore ratio at 10 nm decreases and the pore ratio at 4 nm increases, which is mainly due to the porous wormhole-like alumina occupying part of the cavities of the halloysite.
[0101] Figure 6 The fluorine removal rate comparison chart of the halloysite-based adsorbent HA8-600, the halloysite raw material H, and the composite product HA8 prepared in Example 1 of the present invention under the conditions of a dosage of 0.5 g / L, a fluorine removal time of 6 h, a temperature of 30° C., an initial concentration of the fluorine ion solution C0 of 10 mg / L, and a pH of 4 is shown in FIG. Figure 6 It can be seen that HA8-600 has significantly improved fluorine removal efficiency.
[0102] Figure 7 The figure is a comparison chart of the fluoride removal rate of the halloysite-based adsorbent HA8-600 prepared in Example 1 of the present invention in water bodies with different pH values under the conditions of a dosage of 0.5 g / L, a fluoride removal time of 6 h, a temperature of 30°C, and an initial fluoride ion solution concentration C0 of 10 mg / L. Figure 7 It can be seen that the halloysite-based adsorbent prepared in Example 1 of the present invention has a good fluorine removal rate in a wide pH range, but is better under acidic conditions. Because too high an adsorption rate is not conducive to studying the influence of various factors on the adsorption performance of the sample, pH=4 is selected when studying the influence of other factors, and pH=3 is selected when studying the optimal adsorption performance.
[0103] Figure 8 Under the conditions of pH 4, defluorination time of 6 h, temperature of 30 ° C, and initial concentration of fluoride solution C0 of 10 mg / L, the fluoride removal rate (Removal) and equilibrium adsorption capacity (q) of the halloysite-based adsorbent prepared in Example 1 of the present invention at different dosages are shown in Table 1. e ) comparison chart. Figure 8It can be seen that the fluorine removal efficiency is the lowest when the minimum dose of halloysite-based adsorbent is 0.125 g / L. As the dose increases to 1 g / L, the fluorine removal efficiency increases, mainly because the adsorption active sites increase with the increase in adsorbent dose; and when it further increases to 3 g / L, the adsorption efficiency gradually decreases, which may be caused by the excessive amount of defluorinating agent causing the particle overlap phenomenon to intensify. Equilibrium adsorption capacity q e It is gradually decreasing. The main reason is that as the amount of defluoridation agent increases, the active sites also increase. However, the concentration of fluoride ions in the solution is constant, so the equilibrium adsorption capacity gradually decreases. In studying the influence of other factors, in order to take into account both the fluoride ion removal rate and the equilibrium adsorption capacity, a dose of 0.5 mg / L was selected; and a higher dose can be selected when studying the optimal adsorption rate.
[0104] Fig. 9 The figure is the effect of coexisting anions in water on the fluoride removal performance of the halloysite-based adsorbent prepared in Example 1 of the present invention under the conditions of a dosage of 0.5 g / L, a pH value of 4, a fluoride removal time of 6 h, a temperature of 30°C, and an initial concentration of fluoride ion solution C0 of 10 mg / L. Fig. 9 It can be seen that the several anions studied so far have no obvious effect on the performance of the gangue-based defluoridation agent, indicating that the halloysite-based adsorbent has good adsorption selectivity.
[0105] Fig.10 This is a comparison chart of the defluorination performance of the halloysite-based adsorbent HA8-600 prepared in Example 1 of the present invention and the commercial activated alumina defluoridation agent under a more optimal pH condition (pH=3) (other conditions: defluorination time is 6h, temperature is 30°C, and the initial concentration of fluoride ion solution C0 is 10mg / L). Fig.10 It can be seen that the fluorine removal efficiency of commercial activated alumina decreases significantly when the adsorption dosage decreases from 3g / L to 0.5g / L, but the fluorine removal efficiency of HA8-600 remains almost unchanged, indicating that a small amount of HA8-600 can achieve good fluorine removal effect, and the cost advantage is obvious.
[0106] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a halloysite-based adsorbent, characterized in that: The following steps are involved: The soluble Al 3+ The salt solution is dropped into 50℃~95℃ halloysite and alkali metal Cl - In the suspension formed by the salt solution, the pH value is controlled at 8-11, and the coprecipitation reaction is carried out. 3+ With Cl - Formation of [AlCl4] - The ligand is then hydrolyzed to obtain boehmite-type alumina, which is then loaded on halloysite to obtain a composite product; The composite product is calcined at 400-700° C. to obtain a halloysite-based adsorbent.
2. The preparation method according to claim 1, characterized in that: The alkali metal Cl - Cl in salt solution - The concentration of Al is 0.01-0.2 g / mL, and the soluble Al 3+ Al in salt solution 3+ The concentration of the alkali metal Cl is 10 to 100 mol / mL. - Salt solution and soluble Al 3+ The volume ratio of the salt solution is 1-5:1-5.
3. The preparation method according to claim 2, characterized in that: The halloysite and the alkali metal Cl - The dosage ratio of the salt solution is 0.2-5g:30ml.
4. The preparation method according to claim 1, characterized in that: The coprecipitation reaction time is 10 min to 24 h.
5. The preparation method according to claim 1, characterized in that: The calcination time is 1 to 6 hours.
6. The preparation method according to claim 1, characterized in that: The soluble Al 3+ The salt is one or more of aluminum sulfate, aluminum nitrate, aluminum chloride and alum.
7. The preparation method according to claim 1, characterized in that: After the coprecipitation reaction is completed, centrifugation is performed to obtain a primary product, and the primary product is washed and dried at 50° C. to 60° C. overnight to obtain a composite product.
8. A halloysite-based adsorbent prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the halloysite-based adsorbent according to claim 8 in removing fluoride ions from water.
10. The use according to claim 9, characterized in that: The concentration of fluoride ions in the water body is ≤10 mg / L.
Citation Information
Patent Citations
Zeolite adsorbent and its preparation method
CN101007261A
Defluorination absorbing material based on aluminum base composite oxides and its preparation method and use and special device of the preparation method
CN101507911A
Active aluminum oxide fluoride-removal adsorbing material with different surface characteristics as well as preparation method and application thereof
CN103170302A
Core-shell catalyst as well as preparation method and application thereof
CN113368890A
Hydroxyapatite / halloysite nanotube composite adsorption material as well as preparation method and application thereof
CN114797759A